Use of fiber-section beam elements for modelling the monotonic flexural response of RC jacketed columns. (1st February 2021) - Minafò, Giovanni; Camarda, Gaetano
Highlights: The problem of beams coupled by a non-linear interface is studied. Non-linear static monotonic analyses are performed in OpenSees. Comparisons with the monolithic assumption highlights differences in stiffness and lateral load capacity. Comparisons with experimental results confirm the reliability of the approach. Abstract: The use of reinforced concrete (RC) jacketing is a common technique for retrofitting existing RC columns with poor structural performances. Literature studies highlighted that the relative slip occurring at the interface between the new and the old concrete can affect substantially the flexibility and the strength of the retrofitted member. For this reason, several interface treatments are usually applied, aiming to induce a monolithic behaviour to the column. However, despite the commonness of RC jacketing, a limited number of studies investigated numerical modelling strategies for including these phenomena, especially with reference to the development of numerical models for design-oriented applications. This paper presents the results of a finite element modelling (FEM) approach for evaluating the flexural behaviour of members reinforced with RC jackets. The proposed method takes advantage of fiber-section beam elements connected through a non-linear interface. Monotonic static non-linear analyses are performed and results highlights the differences with the usual assumption of monolithic behaviour. The comparisons with experimental results confirm the reliability of the approach, which allows to obtain accurate results with a substantial reduction of the computational cost with respect to brick-based FEM.